Mapping Thunderstorm Electrical Structure in the Troposphere in Warm Season with VLF/LF Total Lightning Monitoring Data over the Pearl River Delta Region, China - Jianguo Wang; Si Cheng; Li Cai; Yadong Fan; Mi Zhou; Quanxin Li; Yijun Huang (Atmosphere, 2022)
Mapping the thunderstorm electrical structure could provide an effective way for lightning-sensitive facilities protection, such as aircraft and maritime assets. However, the weather radar that is normally used to forecast storms and rainfall mainly detects precipitation in the atmosphere and indicates the existence of liquid raindrops and ice particles by reflectivity. Here, we use intra-cloud events of eight thunderstorm days in the warm season, which are detected by VLF/LF Total Lightning monitoring system, to reveal the thunderstorm electrical structures in the 300 × 300 km area of the Pearl River Delta (PRD) region. The differences in height range in four types of time intervals and three types of intro-cloud events proportions are compared on 16 May. With the proportion between 20% and 80% in the time interval of 15 min, the height distribution and the electrical structure of eight thunderstorm days are clearly exhibited. The positive IC events lie in the average height between 7.5 and 12.4 km, while the negative IC events are located between 5.3 and 11.7 km. The electrical structures show the variations during the evolution process, with a dipole structure in most circumstances, while temporary reversions are identified in the initial and the dissipating stage of thunderstorms, presenting the inverted dipole and the tripole structures.